2023
DOI: 10.3389/fpls.2023.1034421
|View full text |Cite
|
Sign up to set email alerts
|

Integrated use of phosphorus fertilizer and farmyard manure improves wheat productivity by improving soil quality and P availability in calcareous soil under subhumid conditions

Abstract: IntroductionLow soil fertility and high fertilizer costs are constraints to wheat production, which may be resolved with integrating fertilizer phosphorus (P) and farm-yard manure (FYM). Study objectives were to evaluate P source impacts on soil, P efficiency, and wheat growth in a calcareous soil.MethodsTreatments included P fertilizer (0, 17, 26, or 39 kg P ha-1) and/or FYM (0 or 10 T ha-1) in a: 1) incubation experiment and 2) wheat (Triticum aestivum spp.) field experiment.Results and DiscussionSoil organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Soil P effectiveness is an important factor in crop yield response to P fertilization and is often used as a guide for agricultural production ( Buczko et al., 2018 ; Meyer et al., 2020 ; Ibrahim et al., 2022 ). Many studies have shown that P fertilizers with organic materials increase crop productivity by enhancing plant-available P ( Carneiro et al., 2021 ; Jamal et al., 2023 ). In this study, excessively high manure application rates led to a significant reduction in soil P effectiveness, which was the primary reason for the reduced growth of pepper.…”
Section: Discussionmentioning
confidence: 99%
“…Soil P effectiveness is an important factor in crop yield response to P fertilization and is often used as a guide for agricultural production ( Buczko et al., 2018 ; Meyer et al., 2020 ; Ibrahim et al., 2022 ). Many studies have shown that P fertilizers with organic materials increase crop productivity by enhancing plant-available P ( Carneiro et al., 2021 ; Jamal et al., 2023 ). In this study, excessively high manure application rates led to a significant reduction in soil P effectiveness, which was the primary reason for the reduced growth of pepper.…”
Section: Discussionmentioning
confidence: 99%
“…Green manures, also referred to as cover crops, are generally grown at times when soil would otherwise be bare, typically in the period after a crop is harvested or the orchard alleyways ( Lal, 2015 ). The utilization of green manure represents a significant field management strategy that can enhance the effectiveness of soil P and reduce the reliance on mineral P fertilizers ( Li et al., 2015 ; Jamal et al., 2023 ; Ozbolat et al., 2023 ; Zhang et al., 2023 ). According to the study conducted by de Oliveira et al., 2017 in no-tillage onion production of Santa Catarina, Brazil, the incorporation of green manure residues has demonstrated the ability to promptly release soluble inorganic P (P i ) and elevate the availability of P in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…An estimation of more than 90% of rock phosphate produced is used to manufacture synthetic fertilizers (Li et al, 2016). Unfortunately, inorganic P (Pi) application is sparingly available to plants because it is immobilized and gets precipitated with other soil constituents at different pH regimes (Jamal et al, 2023;Johan et al, 2021;Richardson et al, 2009). Consequently, unsystematic applications of chemical fertilizers pose numerous environmental and ecological problems such as eutrophication (Akhtar et al, 2016;Daneshgar et al, 2018;Mihoub et al, 2022;Xia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%